Effect of Phototherapy on Stroke Volume in Newborn Infants with Jaundice - Firouzi, Majid; Sherkatolabbasieh, Hamidreza; Nezami, Alireza; Shafizadeh, Shiva (Journal of Pediatric Intensive Care, 2020)
One of the rare complications associated with phototherapy include redistribution of blood flow that can alter cardiac output in infants. The aim of this study was to evaluate the effects of phototherapy on left ejection fraction in infants with jaundice. Twenty-nine infants admitted in Shahid Madani Children Hospital for receiving phototherapy were included in this study. Echocardiography was performed in the participants, immediately before and 24 hours after the treatment. Nineteen infants were reported to have decrease in the stroke volume following the treatment. The mean levels of stroke volume before and after phototherapy were 6.99 ± 2.17 and 6.55 ± 1.85 L/m2, respectively (p = 0.011). Phototherapy can reduce left ejection fraction in newborn infants with hyperbilirubinemia.
Keywords: phototherapy; stroke volume; echocardiography; newborn